1991
DOI: 10.1016/0035-9203(91)90384-b
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal or vertical transmission of hepatitis B virus? A serological survey in family members of hepatitis B carriers in Singapore

et al.

Abstract: Hepatitis B serology was performed on 270 family members of 78 hepatitis B carriers and hepatitis B e antigen status determined in those found to be HBsAg positive. The mean age of index patients was 38 years (range 3-74) and that of family members was 28 years (range 1-71). 67 family members (25%) were HBsAg positive. The proportions of family members positive for HBsAg and those negative for HBsAg but positive for anti-HBs and/or anti-HBc were 25% and 20% for children, 10% and 68% for spouses, 36% and 26% fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Various factors are related to the risk of intrafamilial transmission of HBV, including exposure to the body fluids of an infected person with skin wounds, and the shared use of personal hygiene items such as toothbrushes, towels, nail scissors and shavers 18,19 . In the present study, the shared use of toothbrush was found to be strongly associated with HBV transmission through household contacts.…”
Section: Discussionmentioning
confidence: 47%
“…Various factors are related to the risk of intrafamilial transmission of HBV, including exposure to the body fluids of an infected person with skin wounds, and the shared use of personal hygiene items such as toothbrushes, towels, nail scissors and shavers 18,19 . In the present study, the shared use of toothbrush was found to be strongly associated with HBV transmission through household contacts.…”
Section: Discussionmentioning
confidence: 47%
“…Most of the previous publications have analyzed pairs of mothers and infants or parents and infants [Esteban, 1959;Bancroft et al, 1971;Merrill et al, 1972;Schweitzer et al, 1972;Mazzur et al, 1974;Papaevangelou et al, 1974;Anderson et al, 1975;Skinkoj et al, 1976;Gerety and Schweizer, 1977;Shiraki et al, 1977;Derso et al, 1978;Lee et al, 1978;Tong et al, 1981;Gussetti et al, 1983;Soulie et al, 1991;Burk et al, 1994;Kuru et al, 1996]. Most publications on the intrafamilial transmission of HBV were also restricted to the generations of parents and children [Hadziyannis and Irwin et al, 1970;Merikas, 1970;Bancroft et al, 1971;Szmuness et al, 1975;Grossman et al, 1975;Koff et al, 1977;Williams et al, 1987;Tan et al, 1991].…”
Section: Hepatitis B Markers In Family Members Of 44 Hbv-carrier Mothersmentioning
confidence: 99%
“…The chronic HBV-carrier state has been shown to be the outcome of the disease in less than 5% after acute horizontal infection [Black et al, 1974;Maupas and Melnick, 1981;Ganem, 1982;Bogomolski-Yahalom et al, 1991;Tan et al, 1991]. In the 44 families, 153 children were identified, who were born to couples with HBV markers.…”
Section: The Risk Of Perinatal Transmission Of Hbv Is Dependent On Thmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV infection is highly endemic in many developing countries, including those in Asia, Africa and the Western Pacific (Hawkes et al, 1981;Hyams et al, 1989;Boutin et al, 1990;Bile et al, 1991;Tan et al, 1991) . In such a setting, most persons are infected in early childhood though both perinatal transmission (mother to infant at birth) and horizontal transmission (close contact with other infected persons) .…”
Section: Introductionmentioning
confidence: 99%